Histone deacetylase inhibitor panobinostat induces calcineurin degradation in multiple myeloma - Imai, Yoichi (JCI Insight, 2016)
Multiple myeloma (MM) is a relapsed and refractory disease, one that highlights the need for developing new molecular therapies for overcoming of drug resistance. Addition of panobinostat, a histone deacetylase (HDAC) inhibitor, to bortezomib and dexamethasone improved progression-free survival (PFS) in relapsed and refractory MM patients. Here, we demonstrate how calcineurin, when inhibited by immunosuppressive drugs like FK506, is involved in myeloma cell growth and targeted by panobinostat. mRNA expression of PPP3CA, a catalytic subunit of calcineurin, was high in advanced patients. Panobinostat degraded PPP3CA, a degradation that should have been induced by inhibition of the chaperone function of heat shock protein 90 (HSP90). Cotreatment with HDAC inhibitors and FK506 led to an enhanced antimyeloma effect with a greater PPP3CA reduction compared with HDAC inhibitors alone both in vitro and in vivo. In addition, this combination treatment efficiently blocked osteoclast formation, which results in osteolytic lesions. The poor response and short PFS duration observed in the bortezomib-containing therapies of patients with high PPP3CA suggested its relevance to bortezomib resistance. Moreover, bortezomib and HDAC inhibitors synergistically suppressed MM cell viability through PPP3CA inhibition. Our findings underscore the usefulness of calcineurin-targeted therapy in MM patients, including patients who are resistant to bortezomib.